2020
DOI: 10.1186/s12931-020-01334-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung volume dependence of respiratory function in rodent models of diabetes mellitus

Abstract: Background Diabetes mellitus causes the deterioration of smooth muscle cells and interstitial matrix proteins, including collagen. Collagen and smooth muscle cells are abundant in the lungs, but the effect of diabetes on airway function and viscoelastic respiratory tissue mechanics has not been characterized. This study investigated the impact of diabetes on respiratory function, bronchial responsiveness, and gas exchange parameters. Methods Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
3
12
0
2
Order By: Relevance
“…Hysteresis is calculated as the ratio G / H , and its value increases because of a proportionally greater increase in G than in H as the lung becomes mechanically more heterogeneous 40 (Figure 3D). Changes in lung function have been documented both in experimental models of diabetes 16 and humans 6,34 . Moreover, our results may suggest the frequent occurrence of compromised lung function in diabetes because it was observed in MD and in the face of slow hyperglycaemic evolution.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Hysteresis is calculated as the ratio G / H , and its value increases because of a proportionally greater increase in G than in H as the lung becomes mechanically more heterogeneous 40 (Figure 3D). Changes in lung function have been documented both in experimental models of diabetes 16 and humans 6,34 . Moreover, our results may suggest the frequent occurrence of compromised lung function in diabetes because it was observed in MD and in the face of slow hyperglycaemic evolution.…”
Section: Discussionsupporting
confidence: 53%
“…G and H may vary because of modification in the rheological properties of lung parenchyma 37 . These changes are initiated by the biochemical and inflammatory cascade triggered by hyperglycaemia, which leads to lung tissue modifications, including remodelling of the extracellular matrix 16,37 . In fact, a higher G indicates a heterogeneous narrowing of distal airways and changes in the intrinsic rheological properties of the parenchyma, 38 while the increment in H depends largely on alveolar collapse 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of pulmonary dysfunction in hyperglycemic status and overt DM was multifactorial [35], including insulin resistance, oxidative stress, elastic fibers remodeling, excessive pulmonary collagens expression, and smooth muscle dysfunction [36][37][38][39]. Singh et al showed hyperinsulinemia-induced activation of β-catenin mediated pulmonary fibrosis and epithelial-mesenchymal transition in mice and human airway smooth muscle cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Clemmer et al showed hyperglycemia was associated with increased pulmonary vascular permeability via the superoxide pathway in obese rats [37]. Südy et al also found that increased pulmonary tissue viscoelasticity was associated with the alveolar collapse in diabetic rats [38]. The hyperglycemic effects on the airway and alveolar regions could result in an increase in pulmonary elastic fiber remodeling, and therefore, reduce pulmonary volume [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%